Normative ideas legal protection to witness and victim in criminal case - Suganda, Atma; Kristiawanto, Kristiawanto; Dewi, Ratna (International Journal Labs, 2024)
Legal protection of witnesses and victims in criminal cases is an important aspect of the Indonesian criminal justice system. This is due to the crucial role of witnesses and victims in assisting law enforcement and achieving justice for victims. However, legal protection for witnesses and victims in Indonesia still has weaknesses, with many cases remaining undisclosed due to a lack of adequate evidence. This study aims to analyze normative ideas regarding legal protection for witnesses and victims in criminal cases. The research method used is the normative juridical method. The data collection technique in this study involves a literature study. The data analysis used in normative law research is qualitative analysis. The results of the study show that normative ideas are needed to strengthen legal protection for witnesses and victims in criminal cases. These ideas include strengthening the legal foundation through expanding the scope of protection, strengthening protection institutions, increasing public awareness, reforming the criminal justice system that focuses on developing a victim-centered justice system, and the use of technology in legal protection for witnesses and victims. Through the strengthening of legal protection, it is hoped that witnesses can give important testimony without fear, which ultimately supports the creation of a fair legal system and provides effective legal protection for all Indonesian citizens.